Factors associated with inappropriate urine culture orders in hospitalized patients with indwelling urinary catheters - Ramez Azzam; Nicole C. Nicolsen; Jacob W. Pierce (Antimicrobial Stewardship & Healthcare Epidemiology)
Urine cultures ordered for patients with indwelling urinary catheters might lead to reporting of non-clinically significant catheter-associated urinary tract infections (CAUTIs) or asymptomatic bacteriuria to the National Healthcare Safety Network (NHSN). We examined factors associated with inappropriate urine cultures orders leading to reporting of non-clinically significant CAUTIs to NHSN.